2020
DOI: 10.3390/agriculture10050164
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Variation and Implications on Repellency Activity of Tephrosia vogelii (Hook f.) Essential Oils Against Sitophilus zeamais Motschulsky

Abstract: The aim of this research is to characterize the variation in the chemical composition of Tephrosia vogelii essential oils from different locations and to investigate the repellency of essential oils against Sitophilus zeamais. Chemical variability in the components of T. vogelii essential oils from eastern Uganda was identified using principal component analysis (PCA) and agglomerative hierarchical clustering (AHC). Based on the profiles of the compounds of the farnesene family, three chemotypes were found: fa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…For example, plants such as Tephrosia vogelii and Lippia javanica (Burm. f.) exhibited an extreme variation of bioactive principles [56]. Also, the chemical variability in the essential oil composition of the T. vogelii plant sampled from diferent locations in eastern Uganda has been reported [56].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…For example, plants such as Tephrosia vogelii and Lippia javanica (Burm. f.) exhibited an extreme variation of bioactive principles [56]. Also, the chemical variability in the essential oil composition of the T. vogelii plant sampled from diferent locations in eastern Uganda has been reported [56].…”
Section: Discussionmentioning
confidence: 98%
“…f.) exhibited an extreme variation of bioactive principles [56]. Also, the chemical variability in the essential oil composition of the T. vogelii plant sampled from diferent locations in eastern Uganda has been reported [56]. Te variation in the essential oils of the plants can be attributed to the extraction methods, seasonal variation, and chemotaxonomic factors [56,57].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…For example, cinnamon EO sterilizes Escherichia coli and Staphylococcus aureus with minimum bactericide concentrations of 4.0 and 2.0 mg mL −1 , respectively 13 . Furthermore, EOs isolated from Clinopodium tomentosum , Clinopodium nubigenum, 10 Croton rudolphianus , Tephrosia vogelii , Lippia graveolens , Cymbopogon citratus , and Mentha piperita L. have been shown to have repellent or insecticidal activities against Sitophilus granarius , Callosobruchus maculatus , Sitophilus oryzae , and Tribolium castaneum 14‐17 …”
Section: Introductionmentioning
confidence: 99%
“…13 Furthermore, EOs isolated from Clinopodium tomentosum, Clinopodium nubigenum, 10 Croton rudolphianus, Tephrosia vogelii, Lippia graveolens, Cymbopogon citratus, and Mentha piperita L. have been shown to have repellent or insecticidal activities against Sitophilus granarius, Callosobruchus maculatus, Sitophilus oryzae, and Tribolium castaneum. [14][15][16][17] Limonene, a terpene, is the main chemical constituent of many EOs including Mentha spicata and Anethum sowa, 18 and has many potential applications as an insecticide, repellent, and antimicrobial agent. 19 Although a previous study showed that CYP6MS1 may be associated with the metabolism of terpenes, 20 few studies have evaluated the mechanisms mediating the insecticidal activities of limonene.…”
Section: Introductionmentioning
confidence: 99%